2016
DOI: 10.1103/physreve.93.020202
|View full text |Cite
|
Sign up to set email alerts
|

Spiral wave chimeras in locally coupled oscillator systems

Abstract: The recently discovered chimera state involves the coexistence of synchronized and desynchronized states for a group of identical oscillators. In this work, we show the existence of (inwardly) rotating spiral wave chimeras in the three-component reaction-diffusion systems where each element is locally coupled by diffusion. A transition from spiral waves with the smooth core to spiral wave chimeras is found as we change the local dynamics of the system or as we gradually increase the diffusion coefficient of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 34 publications
4
31
0
Order By: Relevance
“…When the nonlocality level is low (small values of the coupling range), the system demonstrates complex spatiotemporal structures, namely spiral wave and target wave chimeras as in [7]. The features of the spiral wave chimeras are similar to the ones in the other models [7,17,42,22,40,15]. For example, there is no characteristic bell-like spatial distribution of the mean oscillation frequency.…”
Section: Discussionmentioning
confidence: 88%
“…When the nonlocality level is low (small values of the coupling range), the system demonstrates complex spatiotemporal structures, namely spiral wave and target wave chimeras as in [7]. The features of the spiral wave chimeras are similar to the ones in the other models [7,17,42,22,40,15]. For example, there is no characteristic bell-like spatial distribution of the mean oscillation frequency.…”
Section: Discussionmentioning
confidence: 88%
“…• Although we have only discussed systems with nonlocal coupling, it has recently been found that systems with just local coupling can also support chimera states [27,32]. A self-consistency derivation of the form in [27] may be possible for spiral waves in locally coupled two-dimensional networks, and solutions of the resulting self-consistency equation might be followed using the same techniques used in this paper.…”
Section: And 22)?mentioning
confidence: 99%
“…Recently, various synchronization scenarios in multiplex and multilayer [23][24][25][26][27][28][29][30][31] networks were studied, such as generalized synchronization [32], inter-layer (external and mutual) synchronization [33][34][35][36][37][38], relay (remote) synchronization [39,40], explosive synchronization [41][42][43][44]. Among a large variety of chimera states [35,, here we concentrate on so-called "spiral wave chimera structures" which are observed in 2D ensembles of coupled nonlinear oscillators [10,22,[73][74][75][76][77][78][79][80][81][82][83][84][85][86]. These were typically found in the case of nonlocal coupling topology of network elements.…”
Section: Introductionmentioning
confidence: 99%